Pengaruh Partisipasi Anggota dan Kualitas Pelayanan Dengan Variabel Moderasi Pendidikan Perkoperasian Terhadap Pengembangan Usaha Koperasi - Widya, Widya; Fikri, Aula Ahmad Hafids Saiful; Robi, La (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the influence of member participation and service quality on the development of cooperative businesses at SMA Negeri 1 Sembakung, with cooperative education as a moderating variable. Low member participation and service quality are often major obstacles to the development of school cooperatives, so this study aims to examine the strategic role of cooperative education in moderating this relationship. Using a quantitative causal-associative approach, this study involved 78 respondents from a population of 248 cooperative members (teachers, educational staff, and students) through purposive sampling. Data were collected using questionnaires and analyzed using multiple regression and moderation regression. The results indicate that member participation and service quality have a significant and positive effect on business development. Additionally, cooperative education was found to significantly moderate the relationship between the two variables. In conclusion, enhancing cooperative education is crucial for optimizing member participation and service quality, which ultimately drives sustainable cooperative business development.